Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Kinerja Pegawai Melalui Semangat Kerja Sebagai Variabel Intervening Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kota Bukittinggi - Gina Salsabilla; Ramdani Bayu Putra; Nila Pratiwi; Hasmaynelis Fitri (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This research aims to determine the extent of the influence of Competency and Work Discipline on Employee Performance, with Work Morale as an intervening variable in the Dinas Pekerjaan Umum dan Penataan Ruang Kota Bukittinggi. The observed phenomenon shows that the performance of employees at the Dinas Pekerjaan Umum dan Penataan Ruang Kota Bukittinggi has not reached the predetermined targets, resulting in employee performance still not being optimal. This research method uses quantitative methods. The data collection method used was a questionnaire with a population and sample of 61 employees at the Bukittinggi City Public Works and Spatial Planning Department. The analytical method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. Based on the results of the hypothesis testing that has been carried out, it is concluded that: Competency has a positive and insignificant effect on Work Morale, Work Discipline has a positive and insignificant effect on Work Morale, Competency has a negative and insignificant effect on employee performance, Work Discipline has a negative and insignificant effect on Employee Performance, Work Discipline has a positive and significant effect on Employee Performance, Competency has a positive and insignificant effect on employee performance through work morale as an Intervening variable, Work Discipline has a positive and insignificant effect on employee performance through work morale as an Intervening variable.